2013
DOI: 10.3389/fnmol.2013.00033
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs in nociceptive circuits as predictors of future clinical applications

Abstract: Neuro-immune alterations in the peripheral and central nervous system play a role in the pathophysiology of chronic pain, and non-coding RNAs – and microRNAs (miRNAs) in particular – regulate both immune and neuronal processes. Specifically, miRNAs control macromolecular complexes in neurons, glia and immune cells and regulate signals used for neuro-immune communication in the pain pathway. Therefore, miRNAs may be hypothesized as critically important master switches modulating chronic pain. In particular, und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 147 publications
(203 reference statements)
0
47
0
Order By: Relevance
“…Different disease processes, such as peripheral nerve injury, inflammatory diseases, cancer, and spinal cord injury show an alteration in miRNA expression suggesting that novel treatments could developed to respond to this alteration. Specific miRNAs may develop as new molecular targets for pain prevention and relief [64]. Sequencing of miRNA utilized to identify miRNAs in primary sensory neurons related to neuropathic pain [65].…”
Section: Mirnas Therapy For Treating Neuropathic Painmentioning
confidence: 99%
“…Different disease processes, such as peripheral nerve injury, inflammatory diseases, cancer, and spinal cord injury show an alteration in miRNA expression suggesting that novel treatments could developed to respond to this alteration. Specific miRNAs may develop as new molecular targets for pain prevention and relief [64]. Sequencing of miRNA utilized to identify miRNAs in primary sensory neurons related to neuropathic pain [65].…”
Section: Mirnas Therapy For Treating Neuropathic Painmentioning
confidence: 99%
“…Several studies identified a deregulation of miR-29a/b in pain conditions such as in spinal dorsal horn-induced muscle inflammation, complex regional pain syndrome (CRPS), and chronic constriction injury. 84,85 However, the target proteins of miR-29a/b and their subsequent regulatory mechanisms in pain processing are not clearly defined.…”
Section: Activity-dependent Regulation Of M Icrornas In Pain Processingmentioning
confidence: 99%
“…miRNAs are known to play an important role in many diseases [7] and their stability in bodily fluids make them highly suitable as potential biomarkers [8]. Recent reviews have catalogued the studies linking miRNAs to various pain conditions, and miRNAs likely play a role in the development of chronic pain owing to their alteration of gene expression [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies that attempt to pursue similar molecular biomarkers between animals and humans may provide valuable information to align preclinical studies with human outcomes. Several studies have examined miRNA expression in the dorsal root ganglion (DRG), trigeminal ganglion, and spinal cord resulting from inflammatory pain models such as complete Freund's adjuvant (CFA), capsaicin, and carrageenan, as well as neuropathic pain models such as spinal nerve ligation (SNL), spared nerve injury (SNI), chronic constriction injury, and sciatic nerve crush [9][10][11][12][13][14]. However, changes in miRNA expression in whole blood from these models have not previously been reported.…”
Section: Introductionmentioning
confidence: 99%